2018
DOI: 10.1101/427989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A FASII inhibitor prevents staphylococcal evasion of daptomycin by inhibiting phospholipid decoy production

Abstract: 30Daptomycin is a treatment of last resort for serious infections caused by drug-resistant Gram-positive 31 pathogens such as methicillin-resistant Staphylococcus aureus. We have shown recently that S. aureus 32 can evade daptomycin by releasing phospholipid decoys that sequester and inactivate the antibiotic, 33 leading to treatment failure. Since phospholipid release occurs via an active process we hypothesised 34 that it could be inhibited, thereby increasing daptomycin efficacy. To identify opportunities f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…We determined that in addition to serum lipoproteins, human serum albumin can serve as a source of eFAs for the bacteria, primarily supplying oleic and linoleic acid (Figure 4A). Although a previous report demonstrated that albumin could sequester exogenous oleic acid from S. aureus, preventing the inactivation of the antibiotic daptomycin, that study used fatty acid-free HSA at 10 mg/L (18). Furthermore, we observed that eFA utilization by S. aureus had an inverse relationship with albumin concentration, where lower HSA levels promoted FFA incorporation whereas higher levels reduced incorporation.…”
Section: Concentration-dependent Effect Of Human Serum Albumin On Efa...contrasting
confidence: 58%
See 4 more Smart Citations
“…We determined that in addition to serum lipoproteins, human serum albumin can serve as a source of eFAs for the bacteria, primarily supplying oleic and linoleic acid (Figure 4A). Although a previous report demonstrated that albumin could sequester exogenous oleic acid from S. aureus, preventing the inactivation of the antibiotic daptomycin, that study used fatty acid-free HSA at 10 mg/L (18). Furthermore, we observed that eFA utilization by S. aureus had an inverse relationship with albumin concentration, where lower HSA levels promoted FFA incorporation whereas higher levels reduced incorporation.…”
Section: Concentration-dependent Effect Of Human Serum Albumin On Efa...contrasting
confidence: 58%
“…This data indicates S. aureus preferably continued to initiate new acyl chains, leading to intermediate accumulation, rather than completely favor FASII bypass with eFA; however, preferred pathways and adaptive mechanisms differ based on experimental conditions such as fatty acid sources or FASII inhibitor concentrations (9,10,55,63,65). AFN-1252 has demonstrated promising synergistic effects when combined with daptomycin by blocking decoy phospholipid release or bacterial growth (18,65). We speculate that the increased UFA ratio of S. aureus in the presence of AFN-1252 could also contribute to enhanced daptomycin activity, as daptomycin targets specific fluid areas of the membrane (15,25,66).…”
Section: Concentration-dependent Effect Of Human Serum Albumin On Efa...mentioning
confidence: 96%
See 3 more Smart Citations